Social Change in Contemporary Islamic Community Development through Transformative Da'wah Praxis - Yasser Muda Lubis (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article on Social Change in Contemporary Islamic Community Development through Transformative Da'wah Praxis is important, because currently transformative da'wah has become a key instrument in responding to contemporary social challenges such as poverty, inequality, and morality issues. kinan, inequality, and morality issues. Furthermore, in practice this article analyzes transformative da'wah models that integrate Islamic values with critical social analysis, and describes its implementation strategy in the context of modern society. Through a literature study approach with descriptive-critical analysis, this research identifies several transformative da'wah models, such as Social Tawhid, Cultural Negotiation, and Sustainable Development. The results show that transformative da'wah not only functions as a means of transmitting Islamic values, but also as a tool for community empowerment and structural transformation. Implementation strategies such as critical-emancipatory education, tiered regeneration, and optimization of alternative media show great potential in expanding the reach and impact of transformative da'wah. The novelty of this research lies in the integration of Islamic values with critical social analysis as well as the use of alternative media and digital technology to create counter narratives to dominant discourses. Thus, transformative da'wah is not only relevant in a religious context, but also a significant force in realizing equitable and sustainable social change.